Soil Type and a Labile C Addition Regime Control the Temperature Sensitivity of Soil C and N Mineralization More than N Addition in Wetland Soils in China - Chunmei Wang; Yunyun Zhang; Yun Li (Atmosphere, 2020)
Wetlands store a large amount of carbon (C) and many are vulnerable to potential global warming. It is critical to quantify the temperature sensitivity of soil nitrogen (N) and C mineralization in response to external labile C or N addition in different types of wetland. Through incubation experiments, the effects of temperature and the addition of N or C on soil C and N mineralization were tested using soils from the Sanjiang Plain wetland (SW), Zoigê alpine wetland (ZW), Yellow River estuary wetland (YW), and Baiyangdian Lake (BL). Our findings showed that temperature, available C and wetland type were dominant factors in the regulation of soil C loss, with soil C in SW and ZW being less stable and poorly resistant to increases in temperature. The response of net N mineralization to N addition showed regional differences. A lack of long-term effects of the deposition of N on soil mineralization suggested that there may be a particular N addition threshold level for changed C and N mineralization. It is predicted that an increase in labile C supply due to elevated carbon dioxide (CO2) and its interactions with wetland types will increase CO2 efflux more than N deposition in wetland soils.